MENAKAR KESIAPAN PUSKESMAS DALAM PENUNTASAN PENANGANAN PENYAKIT: ANALISA DATA RISET FASILITAS KESEHATAN 2019 - Hendarwan, Harimat; Suparmi, Suparmi (UI Scholars Hub, 2023)
The completion of disease treatment at the health center was important for payment of Capitation Based on Fulfillment of Service Commitment (PCFSC/KBPKP) and the Non-Specialist Case Outpatient Referral (NSOR/RRNS) was one of the key indicators. This study aimed to assess public health center readiness in the completion of disease treatment for those stipulated in Ministerial Decree number 514 of the year 2015. This study used Health Facility Research (Rifaskes) data conducted in 2019 with a total of 9831 health centers as observations. Analysis was conducted by comparing the availability of equipment, laboratories, and medicines with existing regulations. Health center readiness in completion of disease treatment differs according to geographical aspects, accreditation status, and financial management. Health centers located in Java, accredited, and holding Regional Public Service Agency (BLUD) financial management had better readiness for disease treatment. Health center readiness for disease treatment still experiencing problems in terms of the availability and adequacy of equipment, supporting examinations, and medicines. Therefore, it is recommended to synchronize and strengthen regulations for determining the type of disease that must be completely treated at the health center; review the type of disease that can be treated; and complete the minimum requirements of equipment, laboratories, and medicines.